2023
DOI: 10.1111/inr.12848
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the psychomotor vigilance of nurses working night shift

Abstract: BackgroundShifts and long working hours decrease the psychomotor vigilance of healthcare workers especially when working night shifts. Working night shifts adversely affects nurses’ health and impacts patient safety.AimThe purpose of this study is to identify factors affecting the psychomotor vigilance of nurses working night shift.MethodsThis descriptive cross‐sectional study was carried out with 83 nurses who were working in a private hospital in Istanbul and voluntarily participated in this study between Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Implementing the PVT alongside subjective measures provides a multifaceted approach to understanding fatigue risk in ATC. Research, such as the study by Peukert and Meyer [13], has documented detrimental effects of night shifts on vigilance for various shift workers, including nurses [14]. Their work, along with the PVT results from this study, highlight the need for further investigation into night shift scheduling and its impact on ATC vigilance.…”
Section: General Discussion and Conclusionmentioning
confidence: 63%
“…Implementing the PVT alongside subjective measures provides a multifaceted approach to understanding fatigue risk in ATC. Research, such as the study by Peukert and Meyer [13], has documented detrimental effects of night shifts on vigilance for various shift workers, including nurses [14]. Their work, along with the PVT results from this study, highlight the need for further investigation into night shift scheduling and its impact on ATC vigilance.…”
Section: General Discussion and Conclusionmentioning
confidence: 63%
“…Implementing the PVT alongside the subjective measures provides a multifaceted approach to understanding fatigue risk in ATC. The PVT has been successfully used in a great variety of se ings and Detrimental effects of the night shift on vigilance have been reported for many types of shift workers, including nurses [10]. More inherent to the area we are discussing, Peukert and Meyer [11] used the PVT to investigate fatigue in air traffic controllers, revealing that fatigue levels varied across shifts and over time.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Based on a comprehensive review of the existing literature, we found that vigilance and EF are impaired among day-night shift-working nurses. However, most studies attribute decreased vigilance and EF to shift nurses' circadian disruptions [12,13]. Te relationship between working hours, nurses' vigilance and EF has been widely underestimated.…”
Section: Introductionmentioning
confidence: 99%